PREMATURE OVARIAN FAILURE - Salimova , Dildora Erkinovna; Obidova, Durdona; Uroqova, Marjona; Sayfullayeva, Mehriniso (Educational Research in Universal Sciences, 2024)
The article presents data on the relationship between the pathogenetic mechanisms of development of menstrual cycle disorders of functional and organic origin and mental disorders from the point of view of the psychosomatic concept. According to the latter, functional disorders of the menstrual cycle are considered psychosomatic, in which gynecological pathology develops as a result of psychopathological disorders. A striking example of such a disease is functional hypothalamic amenorrhea. At the same time, endocrinopathies and premature ovarian failure can also be considered in the paradigm of psychosomatic disorders of ovarian function, due to the high prevalence of anxiety and depressive disorders in this cohort of patients. This review highlights the importance of interdisciplinary collaboration between gynecologist and psychiatrist for the most effective reproductive rehabilitation of patients with amenorrhea. The literature search was carried out in domestic and international databases in Russian and English. Free access to the full text of articles was a priority. The selection of sources was prioritized from 2020 to 2022. However, given the insufficient knowledge of the chosen topic, the selection of sources dates back to 1985.